Brazilian Buffalo Genetic Variability by Cross-Specific Microsatellite Set - Rogberg Muñoz, Andrés (2011)
Buffaloes (Bubalus bubalis) are widely distributed and were introduced to Brazil in 1895. Most of the molecular genetic characterization of buffaloes has been done with cross-specific (cattle) markers, but few of them include Brazilian populations. Nineteen commonly used cattle microsatellites were tested to develop a multiplexed set of microsatellites and characterize Brazilian buffalo. Three PCR mixes were finally developed with the 11 markers that succeed in amplify and were polymorphic (58%). The average number of alleles was 5.42, with an average observed and expected heterocigozity of 0.441 and 0.695, respectively. As it was expected, Brazilian buffalo variability was lower than the previously reported from the domestication centres (China and India), but higher than the seriously selected European populations. The exclusion power calculated for the eleven markers in Brazilian buffalo was 0.9999999996, this allows its use in DNA based traceability.